Maxims Violation of Politeness Principle in the Dialogue of Indonesia’s Candidates Debate - Sri Hartini; Lince Sihombing (Universitas Negeri Medan, 2016)
This thesis deals with maxims violation of politeness principle in Indonesia’s Candidates Debate. The objectives of the study are to describe the types of maxims violation, to elaborate the linguistic realization, and reasons of participants violated maxims of politeness principle. The approach in this study are based on Politeness theory by Geoffrey Leech (1983); tact, generosity, approbation, modesty, agreement and sympathy. The method of this research employed qualitative design. The subjects or the data source are taken from utterances of Presidential Candidates in Dialogue of Indonesia’s Presidential debate. All written data are the transcriptions of recorded observation and interview. The data are taken from you tube. The finding prove that four types of Maxims violation are applied by the President candidates. The writer analyzes that there are 4 maxims are occurred, namely agreement maxim (4%), approbation maxim (4%), modesty maxim (4%), and generosity maxim (15%). the most dominant violated maxim is generosity (15%) out of the total numbers of maxims violation found in the dialogue. The reasons are the participants tried to obtain the benefit from the hearer by delivering the questions expecting to cost the hearer. Key Words: politeness principle, maxim, debate